The Impact of Government Cooking Oil Subsidies on Social Welfare: Elasticity-Based Multimarket Approach - Fatimah, Fatimah; A. Gani, Subhan; Bahri, Syamsul; Meutia, Sri; Syukriah, Syukriah (International Journal of Engineering, Science and Information Technology, 2025)
This paper explores the influence of the Indonesian government's palm cooking oil subsidy policies on the welfare of communities in Aceh Province. The Policy aims to stabilise prices, to support producers, and to increase access to affordable cooking oil for consumers. However, empirical evidence shows that the market price frequently exceeds the government-determined ceiling price, which raises concerns about the Policy's effectiveness. To evaluate the actual impact of the subsidy, this study employs a multimarket analytical model in conjunction with an interest-maximising function approach to identify the optimal subsidy level that maximises social welfare. The analysis includes palm and coconut cooking oil as interrelated commodities, with supply and demand modelled using Cobb-Douglas functions. The study focuses on Elasticity as a key determinant in understanding the effectiveness of the subsidy, given that inelastic behaviour in supply and demand significantly affects the price gap between market equilibrium and subsidy-induced outcomes. Simulation results reveal that the optimal subsidy rates are 16% for palm oil and 26% for coconut oil. Furthermore, sensitivity analysis across four scenarios shows that lower Elasticity necessitates higher subsidies, while higher Elasticity can reduce the required subsidy without diminishing welfare gains. The results indicate that producers enjoy most of the welfare gains, although consumers also benefit from lower market prices. Therefore, a well-calibrated subsidy policy, based on empirical elasticity values and multimarket interactions, can lead to a more balanced welfare distribution. The findings underscore the importance of data-driven policy formulation to enhance efficiency and equity in government subsidy programs. Ultimately, this research recommends that future subsidy frameworks integrate elasticity parameters and economic modelling to ensure affordability and sustainability in essential commodity markets.